Consumers’ Loyalty Related to Labor Inclusion of People with Disabilities - González, Marta; Luis Fernández, José (Frontiers in Psychology, 2016)
Purpose: the purpose of this paper is to show that reporting the corporate commitment to labor exclusion of people with disability correlates with the increase of consumer loyalty. Methodology: It is a theoretical revision that will relate consumer loyalty to three main topics: disability and labor exclusion, responsible consumerism towards disability, and corporate communication to increase loyalty of those consumers that are concerned about this problem. Findings: • Disability is an invisible phenomenon that concerns the whole of human society. So, the exclusion of the collective appears as a great social problem that might be dealt by the companies to be perceived as responsible. • Responsible companies are awarded with the loyalty of the consumers. • Clear corporate information about the commitment with this problem will reinforce the loyalty towards the brand. • This information can be given in an informal way or by following a certification process. The impact of those methods will depend on how disability is understood by each consumer. Originality/value: This paper focuses on a topic usually neglected by companies and even by literature. However, the fact that more and more companies are paying attention to this problem allows us to think that we are facing a social change that will challenge companies.